VSPrep: A General KNIME Workflow for the Preparation of Molecules for Virtual Screening. Issue 10 (6th June 2017) - Gally, José‐Manuel; Bourg, Stéphane; Do, Quoc‐Tuan; Aci‐Sèche, Samia; Bonnet, Pascal
Abstract: Over the past decades, virtual screening has proved itself to be a valuable asset to identify new bioactive compounds. The vast majority of commonly used techniques can be described in three steps: pre‐processing the dataset i. e. small (ligands) and eventually larger (receptors) molecules, execute the method and finally analyse the results. Hence, the preparation of ligands is a critical step for success of commonly used virtual screening approaches such as protein‐ligand docking, similarity or pharmacophore search. We present here a new workflow, VSPrep, for the pre‐processing of small molecules; it is based on freely accessible tools for academics and is integrated within the KNIME platform. It can be used to perform several chemoinformatics tasks such as molecular database cleaning, tautomer and stereoisomer enumeration, focused library design and conformer generation. Additionally, graphical reports of the results are provided to the user as a convenient analysis tool. Abstract :